Extraction of phenolic antioxidants from four selected seaweeds obtained from Sabah - Fu, Carmen Wai Foong; Ho, Chun Wai; Yong, Wilson Thau Lym; Abas, Faridah; Tan, Tai Boon; Tan, Chin Ping (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2016)
Algal have attracted attention from biomedical scientists as they are a valuable natural source of secondary metabolites that exhibit antioxidant activities. In this study, single-factor experiments were conducted to investigate the best extraction conditions (ethanol concentration, solid-to-solvent ratio, extraction temperature and extraction time) in extracting antioxidant compounds and capacities from four species of seaweeds (Sargassum polycystum, Eucheuma denticulatum, Kappaphycus alvarezzi variance Buaya and Kappaphycus alvarezzi variance Giant) from Sabah. Total phenolic content (TPC) and total flavonoid content (TFC) assays were used to determine the phenolic and flavonoid concentrations, respectively, while 2,2-azinobis-3-ethylbenzothiazoline-6-sulfonic acid (ABTS) and 2,2-diphenyl-1-picylhydrazyl (DPPH) radical scavenging capacity assays were used to evaluate the antioxidant capacities of all seaweed extracts. Results showed that extraction parameters had significant effect (p < 0.05) on the antioxidant compounds and antioxidant capacities of seaweed. Sargassum polycystum portrayed the most antioxidant compounds (37.41 ± 0.01 mg GAE/g DW and 4.54 ± 0.02 mg CE/g DW) and capacities (2.00 ± 0.01 μmol TEAC/g DW and 0.84 ± 0.01 μmol TEAC/g DW) amongst four species of seaweed.